Relación entre el aspecto visual, la densidad y la composición química del corcho - CÁCERES ESTEBAN, M J; GARCIA-VALLEJO, M C; GARCIA DE CECA, J L; GONZALEZ-ADRADOS, J R (V Congreso Forestal Español, 2009)
Este trabajo profundiza en el conocimiento de las propiedades del corcho, estudiando la relación entre las dos características principales desde el punto de vista físico (porosidad y densidad) y la composición química del material. Para ello se han tomado dos muestras de tapones naturales de cada una de las tres clases de calidad utilizadas por una industria seleccionada como representativa. Cada una de las dos muestras es de procedencia distinta: Andalucía y Cataluña. En cada tapón se ha determinado la porosidad lateral, la densidad, y la composición química según la metodología de análisis fraccionado clásico. Los resultados de los análisis de la varianza realizados muestran que la composición química del corcho es relativamente homogénea, y no se ve afectada, en general, por ninguno de los dos factores considerados: calidad y procedencia. La excepción es el contenido de suberina, en el que se encuentran porcentajes significativamente mayores para los corchos de mejor calidad que para los de las otras dos clases consideradas y para los procedentes de Cataluña respecto de los de Andalucía. El estudio de las correlaciones entre las variables estudiadas muestra la relación existente entre la presencia de componentes no estructurales (extractivos) y la porosidad, lo que sugiere que la mayor parte de estos compuestos se localizan en los canales lenticulares, y son responsables, además del aumento de la densidad del material.
Keywords: calidad industrial; polifenoles; Porosidad; suberina

INCIDENCIA DE LA MANCHA AMARILLA SOBRE LA CALIDAD DEL CORCHO - GONZALEZ-ADRADOS, J R; GARCIA-VALLEJO, M C; De laVEGA, R; GONZÁLEZ-HERNÁNDEZ, F (III Congreso Forestal Español, 2001)
A brief survey is presented about the state-of-the-art of the influence over cork quality of the so called "yellow stain", a cork anomaly related to non-desired taints in wine. Data coming from an inquiry to the industry on this topic are presented, showing the importance of the problem. A bibliographical search on the mechanical, chemical, and microbiological characterization of cork presenting this defect has also been done. Final results show the changes in the industrial processes and the techniques that are being studied to obtain the cork quality level requested by the wineries
Keywords: Cork; Quality; yellow stain

Low molecular weight phenols in cork stoppers - Pena-Neira, A; Hernández, T; GARCIA-VALLEJO, M C; Cadahía, E; de Simon, B F; Suarez, J A (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 1999)
In this work, we study the low molecular-weight polyphenols in cork stoppers obtained from commercial wine bottles and in samples taken at five stages of the cork stopper manufacturing process. The phenolic compounds (acids, aldehydes, and coumarins) were analyzed by high pressure liquid chromatography with photodiode array detector. The results were studied by statistical methods in order to determine the relationship among these compounds and their variability throughout the industrial processing. Discriminant analysis showed that the phenolic composition allows differentiation of each stage in the manufacture of cork stoppers and the different provenances of stoppers obtained from commercial wine bottles. The results showed wide variations in phenolic content among cork stoppers within each region and each winery.
Keywords: Cork; phenolic compounds; stopper manufacturing

Variability of suberin composition of reproduction cork from Quercus suber throughout industrial processing - Conde, E; GARCIA-VALLEJO, M C; Cadahía, E (HOLZFORSCHUNG, 1999)
The chemical composition of suberin was studied in cork planks from three different trees of Spanish Quercus suber at four different stages of the industrial processing of first transformation: stripping (a), first rest (b), boiling followed by open air rest (c1) and boiling followed by store-room rest (c2). The monomeric composition was determined by gas chromatography/mass spectrometry in the product of depolymerization of the free of extractives cork with sodium methoxide-methanol. The average concentrations of the main monomers were: 1-alkanols (C-20-C-26) 4.17 %; alkanoic acids (C-20-C-26) 5.99 %; alpha, omega-alkanedioic acids (C-16-C-24) 6.20 %; omega-hydroxy-alkanoic acids (C-20-C-26) 29.41 %; erythro- and threo-9, 10-dihydroxyoctadecanedioic acids 6.76 %, erythro- and threo-9,10,18-trihydroxyoctadecanoic acids 9.50 %, 9,10-epoxy-18-hydroxyoctadecanoic acid 2.72 % and 9,10-epoxy-octadecanedioic acid 2.93 % and ferulic acid 5.05 %. Significant differences were observed between samples taken at the stripping and after boiling with store room rest, and both groups of samples differed from those picked after the other two processing stages. Ten components were selected as providing the greatest discrimination among stages: 9-octadecenedioic, 18-hydroxy-9-octadecenoic, eicosanedioic and 9,10-epoxy-18-hydroxy-octadecanoic acids, tetracosanol, and five unidentified components.
Keywords: Cork; industrial processin; Quercus suber; suberin